Esquizencefalia: una causa poco común de convulsiones - Catarina Medeiros; Rita Serras Jorge (Sociedade Galega de Medicina Interna, 2023)
Adults' seizures can have many causes. We presented a 50-years-old female that came to emergency department with altered mental stat. Blood tests didn´t have any changes. Brain-MRI showed malformative syndrome, open-lipp schizencephaly in the left frontal-parietal cerebral hemisphere, hypoplasia of the left cerebellar hemisphere and ventriculomegaly. This is a rare congenital brain malformation, that can be a cause of epileptic seizures. Treatment is conservative.